Community Empowerment Model to Flooding Risk Reduction in Palembang City (A Case Study of Gotong Royong Program). Issue 1 (August 2021) - Sandy, A; Sriati; Azhar; Siswanto, A
Abstract: Palembang, as the capital city of South Sumatera, is one of the cities in Indonesia that flooded almost every year. The Palembang city government has run several programs to overcome this problem, such as formulating environmental policies, construct pumping plant, and normalization. Moreover, Palembang City Government since 2015 promoted mutual cooperation program called Gotong Royong aimed at tackling waste issue and river rehabilitation. However, the main cause of this problem has not been fully resolved because of poor communication and engagement. Therefore, the purpose of this research is to find out public perception about the Gotong Royong Program and design a model of community empowerment to flooding risk reductionin Palembang City. Data were collected by deep interviews, documentations, and observations. The results of the research suggest that if Gotong Royong are to proliferate, close attention must be paid to public participation, attitudes, and knowledge towards flood management, collaboration among local government, communities, and NGOs.